25‐Hydroxyvitamin D concentrations and risk of venous thromboembolism in the general population with 18 791 participants. Issue 3 (13th March 2013) - Brøndum‐Jacobsen, P.; Benn, M.; Tybjærg‐Hansen, A.; Nordestgaard, B. G.
Summary Background Vitamin D has potential antithrombotic effects, suggesting that vitamin D analogs could be used as adjunctive antithrombotic agents. However, epidemiologic evidence of an association between reduced 25‐hydroxyvitamin D concentrations and the risk of venous thromboembolism is lacking. Objectives To test the hypothesis that reduced plasma 25‐hydroxyvitamin D concentrations are associated with an increased risk of venous thromboembolism in the general population. Methods We prospectively studied 18 791 participants from the Copenhagen City Heart Study and the Copenhagen General Population Study. During up to 30 years of follow‐up, 950 participants were diagnosed with venous thromboembolism. Plasma 25‐hydroxyvitamin D concentrations were adjusted for seasonal variation. Results The cumulative incidence of venous thromboembolism as a function of age increased with decreasing tertiles of seasonally adjusted plasma 25‐hydroxyvitamin D (log‐rank trend: P = 4 × 10−4). On comparison of participants in the lowest and the highest tertile of plasma 25‐hydroxyvitamin D concentrations, the crude risk estimate in a model adjusted for age and sex was a 37% (95% confidence interval [CI] 15–64%) increased risk of venous thromboembolism. The corresponding risk increase in a model adjusted for age, sex, body mass index, smoking and cancer was 26% (95% CI 5–51%), and in a multivariable‐adjusted model also including physical activity, hormone replacement therapy, menopausal status, oral contraception use and lipid‐lowering therapy it was 28% (95% CI 6–53%). Furthermore, corresponding risk increases with attempts to correct for regression dilution bias were 103% (95% CI 37–202%), 70% (95% CI 14–155%) and 73% (95% CI 15–160%) in the three models, respectively. Conclusion In these large general population studies, we observed a stepwise increasing risk of venous thromboembolism with decreasing tertiles of seasonally adjusted plasma 25‐hydroxyvitamin D concentrations.